Pengaruh pembacaan al-quran terhadap kesehatan mental individu - Solikhah, Anggun (Maliki Interdisciplinary Journal, 2025)
In the modern era, mental health disorders such as stress, anxiety, and depression have become serious challenges faced by many individuals. Academic pressure, work demands, and excessive exposure to digital media intensify these issues and encourage people to seek more holistic forms of intervention. This study aims to analyze the influence of Qur’anic recitation on mental health through three main dimensions: psychological, spiritual, and physiological. The findings show that reading the Qur’an can reduce stress and anxiety by enhancing self-regulation, improving emotional management, and strengthening a sense of meaning in life. Spiritually, the recitation and contemplation of Qur’anic verses reinforce one’s connection with God, foster inner peace, and cultivate values such as trust in God (tawakkul), patience, and gratitude, which support mental resilience. Physiologically, the rhythm and vibration of Qur’anic recitation influence the parasympathetic nervous system, lower stress hormones, and induce bodily relaxation. This study concludes that Qur’anic recitation is an effective, accessible, and relevant form of spiritual healing for managing modern psychological pressures. The novelty of this study lies in its comprehensive approach that integrates biological, psychological, and spiritual dimensions to understand the therapeutic effects of the Qur’an.